(untitled) (Latakia University Journal -Basic Sciences Series, 2019)
Uncontrolled disposal of produced water from oil and gas industry in the environment involves the environmental hazard like contamination soil by NORM and increase the radiation exposure to terrestrial gamma radiation by workers and public. the study aims to measure radiation levels in the drainage zone and vicinity in the field of crude oil storage tanks in the site of Syrian company for oil transport in Banyas. Terrestrial gamma radiation dose was measured, the values ranged between 0.02 – 0.24 µSv.h-1. The radioactivity concentrations of NORM were determined for Ra226, Th232, K40 by gamma spectroscopy using HPGe detector in surface soil samples taken from three sites, two of them recorded the highest rate of radiation dose, while the third recorded the rate of radiation background. The Ra226, K40, Th232highestconcentrations in the soil samples were found to be 210, 213 and 55.9 Bq.kg-1, respectively. Radiation indexes were estimated. The present results were compared with results published in different countries.